2019
DOI: 10.1108/jhti-02-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Share and share alike?

Abstract: Purpose The growing trend for online peer-to-peer commerce has changed the way consumers purchase and exchange products and services across a wide variety of industries, including the craft beer industry. The lack of large scale distribution channels for local breweries has led to a growing market for social exchanges across the country. However, these barter systems remain more obscure compared to their mega counterparts in monetary exchange systems. The purpose of this paper is to evaluate how the set-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The analysis conducted allowed to conclude that socio-demographic aspects and characteristics of stay and use were shown to have different impacts on the different motivations presented for choosing Airbnb as an accommodation option, highlighting the relevance of the analysis carried out. This research is coherent with investigations conducted by other authors in the field, such as Ampountolas (2019), Muñoz-Leiva et al (2018) and Whalen et al (2019), which also highlighted the importance of individual characteristics on the decision-making process in the hospitality area.…”
Section: Practical Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…The analysis conducted allowed to conclude that socio-demographic aspects and characteristics of stay and use were shown to have different impacts on the different motivations presented for choosing Airbnb as an accommodation option, highlighting the relevance of the analysis carried out. This research is coherent with investigations conducted by other authors in the field, such as Ampountolas (2019), Muñoz-Leiva et al (2018) and Whalen et al (2019), which also highlighted the importance of individual characteristics on the decision-making process in the hospitality area.…”
Section: Practical Implicationssupporting
confidence: 90%
“…In particular, the study offers insights into the cognitive factors that determine individuals' decision to use home sharing platforms, and managers should attend to these factors and consider different marketing strategies when planning to market a technology in different countries. Additionally, sharing economy platforms are encouraged to continue to investigate ways to assist their customers (Whalen et al , 2019). Thus, the paradigm shift to a more individual experience can now be closely analysed by the owners of this kind of platforms to better fit this new generation of home-sharing users.…”
Section: Discussionmentioning
confidence: 99%
“…Results of H1 indicated that overall secondary packaging style did not have a direct influence on respondents' willingness to buy. These findings further highlight that the product, in this case craft beer, is the most influential driver of behavioral intentions (Whalen et al, 2019). To date, much of the research that has assessed behavioral intentions (i.e.…”
Section: Academic Implicationsmentioning
confidence: 65%
“…First and foremost, there is a need for hospitality, tourism, and retail researchers to look further into legislative issues that negatively impact various stakeholders, especially when these issues influence multiple multi-billion-dollar industries. Beer is a product that is bought and sold in various manners (i.e., on-premise, off-premise, own-premise) and a product that has created its own form of tourism (Kraftchick et al, 2014) and under-ground trading marketplace (Whalen et al, 2019). These federal and state laws have myriad effects on local economies, and it is imperative for researchers in these fields to assess the potential positive and negative influences they may have.…”
Section: Discussionmentioning
confidence: 99%